Real-World Experience With Apremilast in Treating Psoriasis. Issue 2 (March 2017) - Mayba, Julia N.; Gooderham, Melinda J.
Background: Clinical trial data have shown apremilast, an oral phosphodiesterase-4 inhibitor, to be efficacious and safe for the treatment of psoriasis. However, little real-world experience using apremilast in the community setting has been documented. Objectives: Many patients with psoriasis are often unresponsive to various treatment modalities, including topical, systemic, and biologic medications. The aim of this chart review was to assess the overall patient experience while using apremilast to treat psoriasis. Methods: A retrospective chart review of electronic medical records was conducted of all patients prescribed apremilast in a community dermatology practice. Results: Of 99 patients who were prescribed apremilast, 81 patients took at least 1 dose. In 63 patients, apremilast improved clinical disease severity, with 37% of patients achieving a body surface area <1%. As a treatment, it was generally well tolerated and caused no serious adverse events. The most commonly reported side effect resulting in discontinuation of treatment of apremilast was nausea and vomiting. Conclusions: Overall, apremilast was a safe and well-tolerated treatment with significant clinical improvement in our patient population.